MEMAAFKAN UNTUK PENYELESAIAN KEJAHATAN MASA LALU: : Analisis Konseptual Perspektif Islam - Siti A'isyah (Fakultas Syariah - IAI Al-Qolam Malang, 2021)
There are two points by which the theme above becomes necessary, first, the urgency of concerning the topic of holding past crime. Second, concerning the concept of forgiveness in accordance with Islamic doctrine. Forgiveness in Islam is firmly accounted, and even regarded as more honorable than retaliation, in holding past crime. Seeing it through maqsid al-syari’ah (the main goal of Islamic law) or mashlahah, and considering Allah’s right (public’s right) and human’s right (personal right), past crime against humanity is against mashlahah, namely mashlahah dlarury; hifz al-nafs. In fiqh, such a crime is included in qisas in which the perpetrator violates both Allah’s right and human’s right. When the victim forgives him, he is free from the responsibility over the personal right but not the public’s one. To fulfill the latest responsibilty, there are three duties to be done; uncovering the historical truth, confession as well as guarantee of non-recurrence in the future.